By His Excellency William Shirley, Esq; captain-general and Governour in Chief in and over His Majesty's province of Massachusetts-Bay in New-England : a declaration of war against the Cape-Sable's and St. John's Indians (Printed by John Draper, printer to His Excellency the Governour and Council, 1744)
Declaration of war against the Cape Sable (Micmac) and St. John's (Malecite) Indians of Nova Scotia and what is now New Brunswick, issued by Gov. William Shirley of Massachusetts Bay with "the advice of Council" in Boston, Oct. 19, 1744.